An Amish garden - Wiseman, Beth, 1962-; Fuller, Kathleen; Goyer, Tricia; Chapman, Vannetta (Thomas Nelson, 2014)
Presents four stories about Amish girls and their gardens, including Beth Wiseman's "Rooted in Love," in which Rosemary, who is trying to support her family but cannot garden, accepts help from Saul, who has loved her for years.